Dental caries among pregnant women in Basrah - Nadhim Kadhim B. D. S. M.Sc., Hala (Journal of Oral and Dental Sciences, 2022)
Background: It has long been suspected that oral diseases could have an effect on pregnancy outcomes in different countries. This study described the dental caries incidence among pregnant women and examined its relationships to their oral health and behavior. Patients and Methods: Two hundred pregnant women were invited to participate in this study. Their ages ranged between 18-40 years. They were inspected at Maternal and Child Hospital as well as the College of Dentistry during the period from January to October 2021. Maternal variables were identified as medical history, previous pregnancy, dental history, presence of any dental complaints during pregnancy and oral hygiene practice. Screening for mothersâ€™ dental caries was carried out using the decayed, missing and filled Teeth index. Results: Among 200 women who delivered during the study period 28 (14%) women had dental caries. Among them 16 (6%) women were treated for dental caries. Mother’s education, women with >3 children in rural regions were significantly associated less with the incidence of dental caries. While, tobacco use or passive smoking has no relationship with occurrence of dental caries. Mothers who did not brush their teeth believed that they could lose a tooth with dental caries only because they were pregnant (66.7%) in comparison to regular twice a day brushing (6.8%). A group of women (56%) were visited dentists regularly either before or during their last pregnancy had less frequently dental caries. Significantly higher dental caries (17.9%) were associated with preterm birth. Conclusions: Women in this study had a high prevalence of dental diseases and knew little about dental care during pregnancy. These results will be helpful in planning oral health programs for pregnant women. Â Â